The primary photoreaction of channelrhodopsin-1: wavelength dependent photoreactions induced by ground-state heterogeneity - Heyne, Karsten; Stensitzki, Till; Muders, Vera; Heberle, Joachim; Schlesinger, Ramona (Frontiers in Molecular Biosciences, 2015)
The primary photodynamics of channelrhodopsin-1 from Chlamydomonas augustae (CaChR1) was investigated by VIS-pump supercontinuum probe experiments from femtoseconds to 100 picoseconds. In contrast to reported experiments on channelrhodopsin-2 from Chlamydomonas reinhardtii (CrChR2), we found a clear dependence of the photoreaction dynamics on varying the excitation wavelength. Upon excitation at 500 nm and at 550 nm we detected different bleaching bands, andspectrally distinct photoproduct absorptions in the first picoseconds. We assign the former to the ground-state heterogeneity of a mixture of 13-cis and all-trans retinal maximally absorbing around 480 nm and 540 nm, respectively. At 550 nm, all-trans retinal of the ground state is almost exclusively excited. Here, we found a fast all-trans to 13-cis isomerization process to a hot and spectrally broad P1 photoproduct with a time constant of (100±50) fs, followed by photoproduct relaxation with time constants of (500±100) fs and (5±1) ps. The remaining fraction relaxes back to the parent ground state with time constants of (500±100) fs and (5±1) ps. Upon excitation at 500 nm a mixture of both chromophore conformations is excited, resulting in overlapping reaction dynamics with additional time constants of <300 fs, (1.8±0.3) ps and (90±25) ps. A new photoproduct Q is formed absorbing at around 600 nm. Strong coherent oscillatory signals were found pertaining up to several picoseconds. We determined low frequency modes around 200 cm-1, similar to those reported for bacteriorhodopsin.